Postmodernisme: Sebuah Dekonstruksi dan Kritik dalam Seni - Miftahul Munir (Institut Seni Indonesia Yogyakarta, 2010)
Postmodernism: A Reconstruction and Criticism of Art. There is no truth that is admitted to be absolute truth or forever truth because everything that correlates to a human being is dynamic. ‘Freedom in art creation’ is needed to guarantee the maximum quality of art making process. When art creation is subject to the power of value or its ethical criteria, it is ‘a veiled oppression process’. In such practices, art is not created for the art itself. What happens there is humanizing the art, moralizing the art, and controlling the art. The characteristic of art is its capacity to free itself from substantive matters. In contemplation, the soul leaves the physical materials and becomes one in the idea of form so that the contemplator experiences exquisiteness or unexquisiteness. This experience is then expressed as a work of art. It is important to be comprehended that each element and each entity may function as an active component in completing human existence in the realm of artistic activities. Keywords: Art critics, human existence, art deconstruction.